PERENCANAAN EKO-DRAINASE KAWASAN PERUMAHAN TEMBALANG PESONA ASRI – SEMARANG - Aji Aflakhi; Venni Budi Cahyani; Dwi Kurniani; Hary Budieny (Jurnal Karya Teknik Sipil, 2014)
As the construction rapidly growing in Indonesia, it causes the land decreasing that can be used to absorb water. This phenomenon will cause an often flood in rainy season and drought in dry season. On the other side, the degradation of land infiltrations as the effect of the changing  of environment. Before the development of the area, the studied area contributes of flow by 0,167 m3/s and volume of run-off equal to 601,2 m3. After theconstruction of Tembalang Pesona Asri regency , the post-development peak of flow and run-off volume increase to 0,573 m3/s and 2061,8 m3. Eco-drainage is defined as efforts to manage the excess of rainfall water by infiltrating into the ground as much as possible or flowing naturally into the river without exceeding the capacity of the river before. Eco-drainage facilities that offeredin this final task included infiltration wells,  and bioretention cell. To restore the flow and volume of runoff around the pre-construction condition, the minimum eco-drainage facilities need 177 units of infiltration wellswith diameter size dimension  of 1,5m depth of 3m, 1300 m2 of bioretention cell which 560 m2 located in Blok R and 740 m2 in Blok A. The construction of this Eco-drainage facility in the Tembalang Pesona Asri regency area can decrease runoff of 1220,419 m3 or 83,5 % from the runoff water cause by the regency construction. This construction of the Eco-drainage facility need approximately 3 months of time with  total cost  Rp. 1.209.126.133,- (one billion two hundred and nine million one hundred twenty-six thousand one hundred and thirty-three rupias). The houses total in Tembalang Pesona Asri Regency are 287 units, so each house’s contribution is equal to Rp. 4.212.983,- (four million two hundred twelve thousand nine hundred eighty three.